STUDENTS’ ERROR IN WRITING TECHNICAL SKILLS BASED ON STAR METHOD AT DTS 2020 - Nusi, Ahmad; Yelliza, Yelliza (Politeknik Negeri Ambon, 2021)
The purpose of this study is to analyze and figure out the students’ error in writing technical skills based on the STAR method. This is really crucial in order to make the students learn from their writing errors based on STAR method and the teacher is strongly able to help them properly. This study was qualitative with a number of subjects were 15 students who joined the Digital Talent Scholarship 2020 by KOMINFO. Content test based on STAR method carried out to identify the error made by the students. The result of this study was categorized into four levels of error. First, the highest percentage of error was T (Task) 36 %. The second was action (A) with 16 % error in writing technical skill with action. Next was the result, R, with 4 % and the last was the situation with 1.3%. Based on the writer observation in teaching bath 3 DTS 2020, error happened because some of the students did not attend the first meeting of the course. The second reason, error could happen because the students are still confused to distinguish between personality traits and introducing self and technical skills. The last reason was the internet connection during the training done via zoom.